2020
DOI: 10.2174/1381612826666200730221035
|View full text |Cite
|
Sign up to set email alerts
|

Plant Compounds for the Treatment of Diabetes, a Metabolic Disorder: NF-κB as a Therapeutic Target

Abstract: Background: The prevalence of diabetes in the world population has reached 8.8 % and is expected to rise to 10.4% by 2040. Hence, there is an urgent need for the discovery of drugs against therapeutic targets to sojourn its prevalence. Previous studies proved that NF-κB serves as central agent in the development of diabetic complications. Objectives: This review intended to list the natural plant compounds that would act as inhibitors of NF-κB signalling in different organs under diabetic condition with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Inactivation of NF-κB directly leads to decreased production of IL-6, TNF-α, IL-1β and other proinflammatory factors, which is capable of relieving LPS-induced ALI ( Dang et al, 2016 ). Several natural compounds present in edible plants and TCM formulations exert anti-inflammatory effects by inhibiting the NF-κB signal pathway ( Seo et al, 2018 ; Sahukari et al, 2020 ). Kong et al have reported that 5-HMF inhibited this pathway in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of NF-κB directly leads to decreased production of IL-6, TNF-α, IL-1β and other proinflammatory factors, which is capable of relieving LPS-induced ALI ( Dang et al, 2016 ). Several natural compounds present in edible plants and TCM formulations exert anti-inflammatory effects by inhibiting the NF-κB signal pathway ( Seo et al, 2018 ; Sahukari et al, 2020 ). Kong et al have reported that 5-HMF inhibited this pathway in RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with UC, elevated NF-κB levels in the nucleus of colonic tissue promote the release of a series of proinflammatory factors encoded by the NF-κB signaling pathway, aggravate the local inflammatory response and tissue damage, and destroy the integrity of the intestinal barrier ( Lu and Zhao, 2020 ). In the T2DM model, increased NF-κB levels widely exist in the intestine, pancreas, and insulin-target organs ( Zhang et al., 2020 ), and are closely related to chronic inflammation, oxidative stress, insulin resistance, and several complications ( Sahukari et al., 2020 ). In addition, multiple other inflammatory signaling pathways may be involved in these two diseases, such as transforming growth factor-β (TGF-β), tumor necrosis factor-α (TNF-α), and peroxisome proliferator-activated receptor (PPAR), among others ( Jurjus et al., 2016 ; Hong et al., 2018 ).…”
Section: The Relationship Between Uc and T2dmmentioning
confidence: 99%
“…Signaling pathways of transcription factors, particularly nuclear factor- κ B (NF- κ B) signaling, are involved in insulin sensitivity [ 27 ]. NF- κ B plays a crucial role in the development of diabetic complications because of its involvement in the expression of genes that are responsible for the damage of organs such as the brain, liver, heart, muscles, endothelium, adipose tissue, and pancreas by inflammation, apoptosis, and oxidative stress [ 28 ].…”
Section: Antidiabetic Pharmacological Research and Related Mechanismsmentioning
confidence: 99%